LOW BACK PAIN CAN BE TREATED WITH SIMPLE EXERCISES AT HOME - Hendrik, Hendrik; Ramba, Yonathan; Arpandjam'an, Arpandjam'an (International Journal of Engagement and Empowerment (IJE2), 2023)
Activities of daily living are the most common activities that cause low back pain in housewives. 75-85% of the population has suffered from low back pain at least once in their lifetime. This problem recurs and continues with more severe problems. One solution to overcome the problem of low back pain is to provide counseling and demonstration of how to overcome low back pain with simple exercises at home. This community service was conducted on housewives with complaints of low back pain as many as 60 people, then given a lecture on proper activities and exercises to overcome low back pain simply. Evaluation was carried out twice (pretest and posttest) by giving a questionnaire that could reveal the level of knowledge and skills as well as observation and question and answer to assess the knowledge and skills of housewives. The results of the implementation of this community service obtained a level of knowledge of housewives of 91.7% and skills of 90%. This activity was carried out with the team. The participants were very active during the activity with a question and answer session